Penanggulangan HIV/AIDS Melalui Jejaring Antar Lembaga Berdasarkan Peraturan Daerah Kabupaten Malang Jawa Timur Nomor 14 Tahun 2008: HIV/AIDS Prevention Through Inter-Institutional Networks Based on Malang Regency East Java Regional Regulation Number 14 of 2008 - Mufidah Ch (Fenomena, 2012)
HIV/AIDS is currently spreading more widely in society. The government and society have responded to this issue by establishing the National Commission for AIDS Prevention (KPAN). Malang Regency issued Local Regulation Number 14 of 2008 on AIDS Prevention, forming KPAN facilitated by the local government budget and building international cooperation. Ironically, the number of infected individuals continues to rise. This research aims to describe the implementation of HIV/AIDS prevention based on Local Regulation Number 14 of 2008. The results highlight supporting factors and obstacles in the implementation through institutional networks in Malang. By applying qualitative methods through interviews, observation, and documentation, this research reveals that the AIDS prevention process through networking is relatively effective. As a result, through this program, services have improved, qualified facilities are provided, KPA's network performance has enhanced, and society's understanding of HIV/AIDS issues has gradually grown, supported by social capital and stakeholder solidarity, although challenges remain. HIV/AIDS saat ini semakin meluas penyebarannya di masyarakat. Pemerintah dan masyarakat telah merespons isu ini dengan membentuk Komisi Penanggulangan AIDS Nasional (KPAN). Kabupaten Malang menerbitkan Peraturan Daerah Nomor 14 Tahun 2008 tentang Penanggulangan AIDS, mendirikan KPAN yang difasilitasi oleh anggaran pemerintah daerah dan membangun kerja sama internasional. Namun ironisnya, jumlah orang yang terinfeksi terus meningkat. Penelitian ini bertujuan untuk mendeskripsikan implementasi penanggulangan HIV/AIDS berdasarkan Perda Nomor 14 Tahun 2008. Hasil penelitian menunjukkan faktor pendukung dan hambatan dalam implementasi melalui jejaring kelembagaan di Malang. Dengan menggunakan metode kualitatif melalui wawancara, observasi, dan dokumentasi, penelitian ini mengungkapkan bahwa proses penanggulangan AIDS melalui jejaring cukup efektif. Hasilnya, melalui program ini, layanan semakin baik, fasilitas yang memadai tersedia, kinerja jejaring KPA meningkat, serta pemahaman masyarakat tentang isu HIV/AIDS berkembang secara bertahap dengan dukungan modal sosial dan solidaritas stakeholder, meskipun masih ditemui hambatan.